Analisis Perbandingan Multi-Protocol Label Switching (MPLS) dan Software-Defined WAN (SD-WAN) sebagai Solusi Jaringan dalam Meningkatkan Optimasi Kinerja Jaringan untuk Digitalisasi Bisnis - Moh Alfaujianto (INTECH, 2025)
The rapid advancement of network technology compels organizations to adopt efficient and scalable networking solutions to support business digitalization processes. This study aims to analyze and compare two major network technologies—Multi-Protocol Label Switching (MPLS) and Software-Defined WAN (SD-WAN)—as network solutions to optimize network performance. The research methodology involves literature review, network simulation, and performance analysis based on parameters such as latency, throughput, reliability, and implementation cost. The results indicate that MPLS offers high reliability and consistent performance, while SD-WAN provides greater flexibility, scalability, and cost efficiency. A combination of both technologies may serve as an optimal solution to support digital business transformation, particularly in addressing complex and dynamic networking challenges. This study is expected to serve as a reference for organizations in selecting the most suitable networking solution for their business needs.